Udejanjanje sodobne doktrine socialnega dela - Mešl, Nina (Socialno delo, 2016)
Today's challenge for social work practice and science is to stimulate conditions for development and strengthening of new practices, based on a contemporary social work doctrine. Our experiences of collaboration with social workers in different contexts have confirmed that they recognize the importance of a shift towards collaborative processes of support and help and that they already espoused these theoretical starting points. Now we have a new task: to co-create practice where it will be evident that collaborative paradigm is also a paradigm-in-use. Understanding the starting points of collaborative social work, it is important to overcome division of working on micro, mezzo and macro levels and search for opportunities in collaborative dialogue of all participants in building a social work practice and science. Throughout the presentation of some results of the project Helping families in the community: co-creation of desired changes for reducing social exclusion and strengthening health, the authors discuss the opportunities for common shift in the field of social work from "what is missing and what should be" to "what is and what could be".
Keywords: collaborative social work; social work; socialno delo; družine; families; soustvarjanje; co-creation; jezik; language; izobraževanje; education